Peningkatan Hasil Belajar Kimia Materi Senyawa Hidrokarbon Siswa SMAS PGRI 1 Maospati Dengan Metode Tutor Sebaya - Wijiastuti, Sulastri (Inovasi: Jurnal Diklat Keagamaan, 2020)
This research is based on the reality in the field, that the understanding of class XI students at SMAS PGRI 1 Maospati about Hydrocarbon Compounds is still very low. The learning method that has been carried out is information discussion and practice questions. Attention of students at first 100%, but increasingly weakened and precisely when practicing student problems such as loss of enthusiasm for learning. Seeing this reality, it is attempted to change the learning method used, namely by using the peer tutor method. This class action research consists of two cycles, each of which has a plan-action-observation-stage reflection. The analysis used is quantitative analysis. The percentage of student attendance in Cycle I and Cycle II was 100%. Classical Learning Mastery in Cycle I was 33.33% and in Cycle II it was 71.43%. These figures indicate that the Peer Tutor method is an appropriate and effective method to improve student learning outcomes on the Hydrocarbon Compound material.